GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 301 species occurrences available in GBIF matching the query: TaxonKey: Niwaella multifasciata (Wakiya & Mori, 1929). The dataset includes 301 records from 12 constituent datasets: 1 records from Fishbase. 1 records from CAS Ichthyology (ICH). 114 records from Fish (KIWE-PI). 163 records from Fish (NSMK-PI). 3 records from Fish (NHMK-PI). 4 records from Fish Collection of Yokosuka City Museum. 1 records from Fish collection of National Museum of Nature and Science. 1 records from Fish Collection of Natural History Museum and Institute, Chiba. 9 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 2 records from Fish Living in Freshwater (KIDR-PI). 1 records from NRM-Fishes. 1 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences